A multicenter prospective study to determine the optimal range of lymph node dissection in pancreatic cancer surgery after neoadjuvant chemotherapy (LYMRIN-Trial): Project study by the Japan Pancreas Society and JON 2302-P - Nana Kimura; Yoshihiro Shirai; Ayaka Itoh; Katsuhisa Hirano; Kazuto Shibuya; Kenta Murotani; Makoto Ueno; Sohei Satoi; Hiroaki Nagano; Junji Furuse; Yoshifumi Takeyama; Tsutomu Fujii (PLoS ONE, 2025)
Introduction Clear evidence regarding the optimal extent of lymph node dissection during pancreatectomy for pancreatic ductal adenocarcinoma (PDAC) is lacking. The index of estimated benefit of lymph node dissection is useful for evaluating the effectiveness of dissection at each lymph node station, but a prospective study is needed for accurate assessment. The aim of the LYMRIN trial is to determine the optimal station of lymph node dissection in pancreatectomy after neoadjuvant chemotherapy using gemcitabine and S-1 (GS) by evaluating the rate of lymph node metastasis and the index of estimated benefit of each type of lymph node dissection. Methods This multicenter prospective interventional trial in Japan that will include a total of 545 PDAC patients (head: 200 patients, body: 165 patients, and tail 180 patients) from 42 leading institutions and hospitals in Japan. Patients diagnosed with resectable PDAC after neoadjuvant GS therapy will be considered eligible for inclusion. Eligible patients will undergo pancreatoduodenectomy or distal pancreatectomy with regional lymph node dissection. The primary endpoint is the percentage of metastases in each lymph node station. Discussion The results of this study will clarify the optimal extent of lymph node dissection, allowing for a more conservative surgical approach, thereby avoiding unnecessary invasive procedures for patients. Trial registration University Hospital Medical Information Network Clinical Trials Registry, UMIN 000051879. Registered 1 October 2023, https://center6.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000059119